2015
DOI: 10.1002/pbc.25544
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic and socioeconomic disparities in survival among children with acute lymphoblastic leukemia in California, 1988-2011: A population-based observational study

Abstract: Background Despite advances in treatment, survival from acute lymphoblastic leukemia (ALL) remains lower among non‐White children than White children in the US. We investigated the association of race/ethnicity and socioeconomic status (SES) with survival. Procedures We analyzed 9,295 Californian children (3,251 Whites, 4,890 Hispanics, 796 Asians, and 358 Blacks) aged ≤19 years diagnosed with a first primary ALL during 1988–2011. We used the Kaplan–Meier method to estimate survival at 1, 5, and 10 years after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
69
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 31 publications
11
69
2
Order By: Relevance
“…We found worse survival among black patients than white patients, consistent with previous studies of AML and acute lymphoblastic leukaemia (ALL) (Abrahão, et al 2015b; Aplenc, et al 2006; Byrne, et al 2011; Patel, et al 2015b; Pulte, et al 2012; Pulte, et al 2013; Rubnitz, et al 2007; Sekeres, et al 2004). Results from several clinical trials at a single institution in the US showed survival in black children with AML to be similar to that in white children (Rubnitz, et al 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found worse survival among black patients than white patients, consistent with previous studies of AML and acute lymphoblastic leukaemia (ALL) (Abrahão, et al 2015b; Aplenc, et al 2006; Byrne, et al 2011; Patel, et al 2015b; Pulte, et al 2012; Pulte, et al 2013; Rubnitz, et al 2007; Sekeres, et al 2004). Results from several clinical trials at a single institution in the US showed survival in black children with AML to be similar to that in white children (Rubnitz, et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…This differs from the results of 2 consecutive clinical trials by the Children’s Oncology Group (patients aged 0 to 21 years) (Aplenc, et al 2006), but is consistent with the population-based study mentioned above (Patel, et al 2015a) that found survival among Hispanics to be similar to that among white patients after adjustment for age (all ages included), and with paediatric clinical trials that showed favourable outcomes among Hispanic patients with AML (Rubnitz, et al 2007). These observations contrast with the worse survival observed among Hispanic children and adolescents with ALL in the US (Abrahão, et al 2015b; Goggins and Lo 2012; Lim, et al 2014; Pulte, et al 2013), and suggest that unfavourable biological characteristics are associated with survival after ALL, (Lim, et al 2014) but may not contribute, to the same extent, to the worse outcomes after AML. In fact, clinical trials have shown favourable cytogenetic characteristics among Hispanic children with AML (Rubnitz, et al 2007).…”
Section: Discussionmentioning
confidence: 81%
“…This could be secondary to a delay in referral and diagnosis or due to underlying genetic differences in relation to prevalence and outcome. Several studies have shown racial and ethnic disparities in healthcare access and outcomes in children 37,38 . Most studies in non-Hispanic White children with JIA-associated uveitis show associations with the HLA-DRB1 allele, and one study highlighted the association of HLA-DR8, but not HLA-DR5, with chronic non-granulomatous anterior uveitis in African Americans 39 .…”
Section: Discussionmentioning
confidence: 99%
“…As this was a record-based study, we did not seek informed consent from individual subjects. The demographic and gestational characteristics of cases and controls have been previously reported (Abrahao et al, 2015; Hall et al, 2016; Heck et al, 2012; Heck et al, 2013b; Heck et al, 2014, 2015; Heck et al, 2013c; Shrestha et al, 2013). …”
Section: Methodsmentioning
confidence: 99%